2009
DOI: 10.20884/1.jm.2009.4.2.68
|View full text |Cite
|
Sign up to set email alerts
|

Penurunan Kadar Amonia, Nitrit, Dan Nitrat Limbah Cair Industri Tahu Menggunakan Arang Aktif Dari Ampas Kopi

Abstract: The tofu industry is one of food industry which the product of organic waste to environment pollution. One of alternative methode which used to overcome tofu industrial waste water pollution is adsorption methode using activated carbon from coffee waste. The aim of this researched is to know about the activated carbon from coffee waste quality which observe of rendemen, water content, ash content, and iodium adsorption, to know optimum contact of time and pH of coffee waste to decrease ammonia, nitrite and nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 0 publications
2
4
0
10
Order By: Relevance
“…In addition to the process of absorbing water hyacinth, the process of reducing ammonia levels was also assisted by the decomposition of organic matter by microorganisms. This causes the organic matter dissolved in the tofu liquid waste to decrease [9]. The results showed that the phytoremediation of water hyacinth by sedimentation was able to make ammonia levels in liquid waste down.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the process of absorbing water hyacinth, the process of reducing ammonia levels was also assisted by the decomposition of organic matter by microorganisms. This causes the organic matter dissolved in the tofu liquid waste to decrease [9]. The results showed that the phytoremediation of water hyacinth by sedimentation was able to make ammonia levels in liquid waste down.…”
Section: Discussionmentioning
confidence: 99%
“…Sedangkan limbah cair, sebagian besar dialirkan langsung air limbahnya ke saluran-saluran pembuangan, sungai ataupun badan air penerima lainnya tanpa diolah terlebih dahulu. Bahan organik yang terdapat pada limbah cair industri tahu apabila berada dalam konsentrasi tinggi, maka akan menimbulkan pencemaran pada lingkungan perairan (Irmanto dan Suyata, 2009) Peraturan Pemerintah RI No.28 Tahun 2011 menyebutkan "pencemaran air adalah masuknya atau dimasukkannnya makhluk hidup, zat, energi dan atau berubahnya tatanan air oleh kegiatan manusia sehingga kualitas air turun sampai ke tingkat tertentu yang menyebabkan air tidak dapat berfungsi sesuai peruntukannya".…”
Section: Pendahuluanunclassified
“…According to Sugiharto in Irmanto and Suyata (2009), coffee grounds include organic materials that can make into activated carbon for use as adsorbents or absorbent materials. Coffee waste is usually more discarded because it is considered waste, but actually, coffee grounds can utilize as activated carbon that will add value function as an adsorbent to increase the carrying capacity to the environment, especially in the climate of peat swamp land.…”
Section: Medical Laboratory Technology Journalmentioning
confidence: 99%